Political Intermarriage between Seljuk’s sultans with Islamic and non-Islamic forces - Nawroz Ali Kakaameen; Nishtman Bashir Muhammad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
In view we can see that the Islamic eras in general and the Seljuk era in particular, we see that historians paid great attention to the political and military life in that era, we do not have enough information in the sources about the intermarriages of the sultans, and this is due to the fact that the research in social life in the ages Islam was linked to a large extent with the traditions prevailing in that era, especially since those traditions were conservative with regard to personal status, including the issue of marriage. Some intermarriages took place in that era, and the Seljuk sultans used intermarriages to assemble and hold the family, and they used it as a means of reconciliation and truce between them and the other side of the prevailing forces in the region, and among those Islamic forces, and other than with the non-state forces. and it was a factor of rapprochement between the two sides and at other times a factor of dissonance and distance between them.